2018
DOI: 10.1007/s11356-018-2953-7
|View full text |Cite
|
Sign up to set email alerts
|

Selected trace elements and metals in groundwater within Permian sediments near Olkusz (Zn-Pb ore mining region, S Poland)

Abstract: The extensive mining of Zn-Pb ores in the Olkusz region resulted in significant changes of both water table level and chemical composition of water in all aquifers in the area. This was caused by intensive dewatering of mining excavations and development of a thick aeration zone reaching 150 m in a central part of the area. That created favorable conditions for oxidation of metal sulfides occurring in the ore-bearing dolomites (Middle Triassic) and started the process of forming readily soluble hydroxysulphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The concentrations of Pb, Zn, and Cd in barley were consistent with the results obtained by Eticha and Hymete [69], who reported that differences in metal contents in barley of different origins might be caused by differences in arable soil types, agrochemical treatment, and environmental pollution. The abovementioned results are in line with the observation that higher PHE concentrations in investigated cereals might be the consequence of the fact that Zn-Pb [70,71] and Cu [72,73] ores are present in the geological background of soils in southern Poland. Moreover, the contents of Pb and Cd reported in wheat and barley grains sampled in northern Poland [74], where non-ferrous geological deposits do not occur, were lower than those identified in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The concentrations of Pb, Zn, and Cd in barley were consistent with the results obtained by Eticha and Hymete [69], who reported that differences in metal contents in barley of different origins might be caused by differences in arable soil types, agrochemical treatment, and environmental pollution. The abovementioned results are in line with the observation that higher PHE concentrations in investigated cereals might be the consequence of the fact that Zn-Pb [70,71] and Cu [72,73] ores are present in the geological background of soils in southern Poland. Moreover, the contents of Pb and Cd reported in wheat and barley grains sampled in northern Poland [74], where non-ferrous geological deposits do not occur, were lower than those identified in this study.…”
Section: Discussionsupporting
confidence: 89%
“…High buffering properties of post-flotation wastes considerably reduce leaching of SO 4 2− , Zn 2+ , Ca 2+ , Mg 2+ and Fe 2+ ions (Postawa and Motyka 2018), but their quantity transferred from the dump remains high. Motyka et al (2005) showed that about 5.0 m 3 of leachate containing, on average, 1400 mg/dm 3 of sulphates infiltrates per minute from the tailing ponds to the underlying sediments.…”
Section: Discussionmentioning
confidence: 99%
“…In the hydrogeological system, it is possible to distinguish Quaternary level related to sands, with a filtration coefficient of 2.5 × 10 −4 m/s, which has been drained by carbonate, karstfissure formations of the Triassic level. Fissured and cavernous diplopora and ore-bearing dolomites occurring in the upper Triassic are very well permeable (10 −5 -10 −4 m/s) (Postawa and Motyka 2018). The layers of Olkusz and Gogolin limestones located below contain marl and clay intercalations, hence their permeability is lower-in the order of 10 −7 -10 −5 m/s.…”
Section: Area Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The described studies were conducted in southern Poland, in the region characterized by a large diversity of geological structures and agricultural and industrial development, as well as anthropogenic pressures. Southern Poland is the area of intense coal mining and processing in the Silesia (Szczepańska and Twardowska 1999;Jończy and Gawor 2017), mining and processing of Zn and Pb ores in the Olkusz area (Krzaklewski et al 2004;Postawa and Motyka 2019), and of Cu ores in the Lower Silesia (Potysz et al 2018). Besides the urban agglomerations of Kraków and Wrocław, the Upper and Lower Silesia Regions are also located in southern Poland, with significant contamination of the environment due to coal-burning heating plant operations, as well as wood and waste burning in poor quality stoves (Kobza et al 2018), not to mention huge local traffic (Adamiec 2017).…”
Section: Correlation and Pcamentioning
confidence: 99%